A Study of Security Limitations in Virtual Local Area Network Implementation - Balasundaram, Arumugam (2003)
Virtual Local Area Network (VLAN) in simple terms is defined as a group of Local Area Network (LAN) that has different physical connections, but communicates as if they are connected on a single network segment.VLAN was developed mainly for the need in network segmenting solution, since network traffic increases in proportional to the network size in the same time to offer additional network security.This technology has now become possible by the advancement of various LAN Switches which offer the VLAN feature.Few researches has been carried out which explain the technology part of the system.This thesis provides a study on VLAN mainly covering the implementation of the system and the security weakness present in certain conditions of implementation.For the VLAN system,an onsite study was conducted to explore the implementation of the system in real life environment followed by a practical test conducted to examine the weaknesses part of the system.The results obtained from the test showed that under certain type of implementation, the security features of the VLAN system can be exploited. Solutions are proposed to further improve the security of the system in which certain part of the solution was gathered upon verifying the issue with the switch manufacturer